Therapeutic efficacy and safety of Unani formulation in patients of Fasaad-e-tashahhum-e-dam (dyslipidemia): a randomized open standard controlled clinical study - Sabahat, Syed; Ul-Islam, Naquib (International Journal of Advances in Medicine, 2021)
Background: Hyperlipidemia which is interchangeably used with the term dyslipidemia essentially refers to the condition of abnormality of lipid levels measured in the blood typically due to the disorder of lipoprotein metabolism. The objective of this study was to determine the therapeutic effect and safety of newly formulated drug on patients with Fasaad-e-Tashahhum-e-Dam (dyslipidemia) and compare it with the effect of Unani formulation and rosavastatin. Methods: The present study was open randomized controlled clinical study. The study subjects were divided in two groups, one group was given test drug (test group) and another group was given control drug (control group). All the patients who qualified the inclusion criteria were randomly placed in either test or control group. Results: In the present study we observed that both the groups were comparable with respect to age, sex lifestyle, family history and mizaj. We found that both Unani formulated drug and standard drug rosavastatin significantly improves the lipid parameters after the treatment with a p value of (<0.001*). Conclusions: We concluded that the overall effect of the proposed Unani formulated drug was found quite fascinating in the treatment of dyslipidemia. Apart from drug safety, visible improvements were evident in objective parameters like cholesterol, triglyceride and LDL, VLD. However, the present study did not revealed that Unani drug is superior to standard drug instead both the treatments are equally effective on the improvement of lipid profile parameters.